The Correlation Between Parenting Style and Picky Eater Habits on The Preschool Students - Suryani, Santi; Agustriyani, Feri; Palupi, Rini; Ardinata, Ardinata (Utan Kayu Publishing, 2022)
Parenting style is one factor in children's character construction. Preschool students have experienced a change in eating behavior that commonly has the picky eater habit. It is the spectrum of feeding difficulties when children refuse to taste new foods, or only want to eat certain foods. This research aims to identify the correlation between parenting style and pick-eater habits among preschool students in Tri Tunggal Jaya Village. The correlation design method was used to analyze the 55 sample respondents in this village. The measurement tools were questionnaires on parenting styles and picky eater habits (CEBQ). Based on the analysis results, parents in the majority of implemented some parenting styles which were permissive parenting as much 28 (50,9%), democratic parenting as much 25 (45,5%), and authoritarian parenting 2 (3,6%). Meanwhile, the picky eaters in the majority showed a rate of 25 (45,5%) and non-picky eaters were 30 (54,5%). According to the gamma testing, it showed that the p-value was 0,000. Thus, it can be concluded that there is a correlation between parenting style in picky eating habits among preschool students in Tri Tunggal Jaya Village, located in the sub-district Penawartama Tulang Bawang regency. Suggestion: for the parents, it will be better to implement a good parenting style for the children in managing childhood eating patterns. Abstrak: Pola asuh adalah salah satu faktor dalam pembentukan karakter anak. Anak usia prasekolah mengalami proses perubahan pola makan dimana anak pada usia ini umumnya mengalami peri laku atau kebiasaan Picky eater yang termasuk kedalam spektrum kesulitan makan (feeding difficulties) dimana anak menolak untuk mencoba makanan baru, atau hanya mau makan makanan tertentu. Tujuan penelitian ini adalah untuk mengidentifikasi hubungan pola asuh Orangtua dengan perilaku Picky eater pada anak usia prasekolah di Desa Tri tunggal jaya. Metode penelitian ini menggunakan desain korelasi dengan jumlah sampel 55 responden di Desa Tri Tunggal Jaya. Alat ukur yang digunakan dalam penelitian ini adalah kuesioner pola asuh dan kuesioner perilaku Picky eater (CEBQ). Dari hasil penelitian didapakan bahwa mayoritas orangtua menerapakan pola asuh permisif yaitu 28 (50,9%), pola asuh demokratis 25 (45,5%), dan pola asuh otoriter 2 (3,6%). Sedangkan mayoritas picky eater 25 (45,5%) dan tidak picky eater 30 (54,5%). Berdasarkan uji gamma didapatkan nilai p value sebesar 0,000 maka dapat di simpulkan ada hubungan antara pola asuh Orangtua kebiasaan memilih-milih makan (Picky eater) pada anak usia prasekolah di Desa Tri Tunggal Jaya Kecamatan Penawartama Kabupaten Tulang Bawang. Saran: Diharapkan kepada orang tua untuk menerapkan pola asuh yang baik dan benar kepada anaknya untuk lebih tepat dalam mengatur pola makan anak.